Aktualisasi Hidden Curriculum Pendidikan Agama Islam dan Implikasinya Dalam Pembentukan Sikap Sosial Siswa - Aqmarina Bella Agustin; Sukirman Sukirman (Alim | Journal of Islamic Education, 2021)
Social attitude is one of the character values that every student must have as a provision in living life in the community to materialize a harmonious and peaceful community condition. The subjects of Islamic Religious education (PAI) have a very strategic role in the cultivation of social attitudes to the students through the development of the PAI hidden curriculum. This research aims to analyze the implementation of the hidden curriculum of Islamic Religious Education (PAI) at State Junior High School 9 Yogyakarta and its implications for the formation of learners ' social attitudes. This type of research used is qualitative descriptive-analytic. The research subject is chosen purposive, which includes the headmaster, vice-principal of student affairs, PAI teacher, guidance and counseling teacher, and learners. Data collection techniques are conducted through interviews, observations, and documentation and then analyzed using the reduction, presentation, conclusion/verification stages. Test the validity of data using the triangulation of resources and techniques. The results concluded that the implementation of the hidden curriculum of PAI in SMP Negeri 9 was realized in the form of implementing the organizational, social, and cultural system. The implementation of the Hidden curriculum of PAI implicates the formation of learners ' social attitudes demonstrated by the respectful attitude of others, not picky in friendship, accustomed to smiles, greetings, and greet everyone, honestly, disciplined, responsible, helping friends in need, and caring for others.